2013
DOI: 10.1016/j.jcpa.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Canonical Wnt/β-Catenin Signalling Pathway is Rare in Canine Malignant Melanoma Tissue and Cell Lines

Abstract: Summary Canine malignant melanoma is a highly aggressive tumour associated with a poor overall survival rate due to both local disease recurrence and its highly metastatic nature. Similar to advanced melanoma in man, canine oral melanoma is poorly responsive to conventional anti-cancer therapies. The lack of sustainable disease control warrants investigation of novel therapies, preferably targeting features specific to the tumour and different from normal cells. The Wnt signalling pathway is known to contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(59 reference statements)
2
10
0
Order By: Relevance
“…As we have previously reported, β-catenin-transcriptional activity is minimal in canine malignant melanoma (Chon et al, 2013). Importantly, a number of in vitro and in vivo studies have demonstrated that BIO, a selective and potent inhibitor of GSK-3β, has anti-oncogenic effects against breast and pancreatic carcinoma stem cells, osteosarcoma, and melanoma (Liu et al, 2011; Cao et al, 2012; Dastjerdi et al, 2012; Nicolaou et al, 2012).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…As we have previously reported, β-catenin-transcriptional activity is minimal in canine malignant melanoma (Chon et al, 2013). Importantly, a number of in vitro and in vivo studies have demonstrated that BIO, a selective and potent inhibitor of GSK-3β, has anti-oncogenic effects against breast and pancreatic carcinoma stem cells, osteosarcoma, and melanoma (Liu et al, 2011; Cao et al, 2012; Dastjerdi et al, 2012; Nicolaou et al, 2012).…”
Section: Discussionsupporting
confidence: 66%
“…However, its effect has not been assessed on canine malignant melanoma cell lines. Therefore BIO may represent a logical compound for evaluation as it has known anti-cancer effects both in vitro and in vivo and it targets a pathway known to be suppressed in canine malignant melanoma (Liu et al, 2011; Chon et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to these low numbers, Bongiovanni et al observed 47% (8/17) of canine OS samples to display nuclear staining; however, in nuclear‐positive samples, less than 10% of nuclei/cells within the sample were positive, indicating that these positive nuclei were very weakly positive. The results of these studies are similar to those evaluating β ‐catenin in human and canine malignant melanoma, in which the presence of cytoplasmic β ‐catenin is frequent, though nuclear β ‐catenin is rare and there is low transcriptional activity in melanoma cell lines . Interestingly, Kuphal and Bosserhoff found serine 33 and 37 residues in β ‐catenin to be hypo‐phosphorylated, likely preventing β ‐catenin from being targeted for ubiquitin‐mediated degradation.…”
Section: Discussionmentioning
confidence: 99%
“…All of the melanoma lines established in our lab were derived from oral melanoma tumor biopsies and were either Stage II (CMSDSc and CMSDTa) or Stage III (CMSDJe and CMSDSh) melanomas. The melanoma cell lines CML-10C2 and CML-6M were derived from a cutaneous primary tumor and a lymph node metastatic lesion, respectively (Chon et al, 2013). The Jones melanoma cell line was derived from a primary tumor.…”
Section: Methodsmentioning
confidence: 99%